2015
DOI: 10.1016/j.jneumeth.2014.07.019
|View full text |Cite
|
Sign up to set email alerts
|

DARPA-funded efforts in the development of novel brain–computer interface technologies

Abstract: The Defense Advanced Research Projects Agency (DARPA) has funded innovative scientific research and technology developments in the field of brain-computer interfaces (BCI) since the 1970s. This review highlights some of DARPA's major advances in the field of BCI, particularly those made in recent years. Two broad categories of DARPA programs are presented with respect to the ultimate goals of supporting the nation's warfighters: (1) BCI efforts aimed at restoring neural and/or behavioral function, and (2) BCI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(79 citation statements)
references
References 79 publications
0
78
0
1
Order By: Relevance
“…First of all, we should mention that some previous roadmaps did pay lots of attention to BCI research in the context of other than medical applications [7,8] and clearly this happened in observations on DARPA funding [13,14]. Moreover, many research projects funded by national or EU funding programs did incorporate research devoted to other than medical BCI related research issues.…”
Section: Vision and Discussionmentioning
confidence: 99%
“…First of all, we should mention that some previous roadmaps did pay lots of attention to BCI research in the context of other than medical applications [7,8] and clearly this happened in observations on DARPA funding [13,14]. Moreover, many research projects funded by national or EU funding programs did incorporate research devoted to other than medical BCI related research issues.…”
Section: Vision and Discussionmentioning
confidence: 99%
“…Surgical placement of FINE around the femoral trunk leads to selective activation of leg muscles, thereby aiding patients who suffer from lower trunk paralysis to stand from a sitting position [134]. Furthermore, the US Department of Defense has investigated the use of FINE in controlling neural prostheses in amputees [90]. Although FINEs have been used in several human studies without any deleterious consequences, FINEs have the potential to compress the nerve, reduce blood flow, or even cause neural damage [116].…”
Section: Flat Interface Nerve Electrodesmentioning
confidence: 99%
“…Studies have demonstrated prosthetic devices with inputs from rat brain circuits as bio-feedback controllers [18], [19]. Since 1970s, cerebellar supervised learning consisting of neural circuit models that optimally control via modulation of firing dynamics [20] have been proposed and have been used by implementing cerebellar network on VLSI chip [21].…”
Section: Introductionmentioning
confidence: 99%